Clinical and prognostic characteristics of BRCA1/2-associated breast cancer depending on the type of mutation: estrogen signaling pathway and secondary tumors - A. I. Stukan; A. Yu. Goryainova; R. A. Murashko; Z. K. Khachmamuk; O. Yu. Chukhray; S. D. Maksimenko; O. A. Goncharova; E. N. Imyanitov; V. A. Porkhanov (ABV-press, 2022)
Background. Currently, there is growth evidence on prognostic and clinical differences in breast cancer (BC) associated with different types of BRCA1 / 2 mutations. At the same time, a triple negative tumor phenotype is not an absolute pathognomonic sign of BRCA1 / 2-associated cancer, where luminal phenotypes are being detected increasingly. In addition, attention is paid to the significance of estrogen signaling mechanism depending on the surrogate tumor type, including a triple negative phenotype due to alternative mechanisms.Objective: to evaluate significance of BRCA1 / 2-mutations in luminal BC subtypes and multiple tumors.Materials and methods. A prospective study conducted in Clinical Oncology Dispensary No. 1 in Krasnodar included 443 patients with breast cancer who underwent a genetic analysis on BRCA1 / 2 genes status by real-time polymerase chain reaction. In diagnostic cases of luminal phenotype and multiple cancers histological material and blood were sent to the N.N. Petrov Research Institute of Oncology of Ministry of Health of Russia to assess the mutation status of the BRCA1 / 2, ATM, CHEK2, NBS1, PALB2 genes by next-generation sequencing (NGS). Statistical analysis of clinical and morphological parameters correlated with mutational status was performed using the IBM SPSS Statistics v.22 statistical package.Results. An interim analysis of data in April 2022 showed that 71 out of 304 breast cancer patients tested by polymerase chain reaction were found to be carriers of BRCA1 gene mutations. NGS method revealed 20 additional mutations of the BRCA1 / 2 genes: 11 BRCA1 mutations and 9 BRCA2 mutations. PALB2 mutation was also detected in 1 patient, NBS1 mutation - in 3, CHEK2 mutation - in 2, ATM mutation - in 2 patients. Out of 91 BRCA1 / 2-associated breast cancer 21 BRCA1-mutated tumors and 9 tumors with BRCA2-mutation demonstrated luminal phenotypes. The median age of breast cancer disease did not differ in BRCA1- and BRCA2-carriers (42 years versus 40 years, p ˃0.05). BRCA1 mutations are associated with poor differentiation (G3), BRCA2 mutations are associated with G2 (p ˂0.001). The BRCA2 mutation is characterized by a luminal tumor phenotype (p ˂0.001). There was no association of BRCA1 / BRCA2 gene mutations with T and N status (p ˃0.05). Of the 91 cases of BRCA-deficient tumors, 30 (33 %) patients had primary multiple cancer: 27 (90 %) with germinal mutation BRCA1 and 3 (10 %) with germinal mutation BRCA2. Contralateral breast cancer in the presence of germinal mutation BRCA1 was detected in 14 patients. The frequency of primary multiple cancer and contralateral breast cancer detection did not depend on the type of BRCA1 / 2 mutations (p ˃0.05).Conclusion. With the primary multiplicity of the tumor process and the luminal subtype of the tumor, the determination of mutations by polymerase chain reaction in real time is clearly insufficient. It is obvious that the NGS method can identify additional pathogenic mutations that predict the clinical course and indicate the possibility of personalizing therapy and the need to test relatives, including tumors with luminal phenotype and tumors of several localizations.